Training of Using Domino Card Game to Teach Fraction for Mathematics Teachers at Junior High Schools in Banjar Regency - Arif Ganda Nugroho; Dina Rafidiyah (Comment: an International Journal of Community Development, 2019)
Mathematics is still considered one of the difficult subjects in junior high schools. Therefore, mathematics teachers must find better way to motivate their students to like the subjects. Fraction is one of the topics that need serious effort to learn it. Therefore, it needs fun way to learn it. Somehow, not all the teachers can understand how to teach fraction in a fun way. Therefore, training about using domino card games to teach fraction for Mathematics teacher at junior high school was held in SMPN 1 Martapura. There were 46 teachers joined the event. The lecturer in Mathematics Education organized the training and the result is most of the teachers wanted to apply it in their class later. The aim of this community service is to encourage the junior high school teachers to use fun ways to teach mathematics rather than to use the conventional way to use LKS (worksheet book).